2020
DOI: 10.1155/2020/5681703
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics and Power Generation on a New Bistable Piezoelectric-Electromagnetic Energy Harvester

Abstract: This paper focuses power generation and nonlinear dynamic behaviors on a new bistable piezoelectric-electromagnetic energy harvester. Three different kinds of piezoelectric cantilever beam structures, which include the monostable piezoelectric cantilever beam, the bistable piezoelectric cantilever beam with spring and magnet, and the bistable piezoelectric cantilever beam with spring, magnet, and coil, are designed. The power generation efficiency and dynamic behaviors for each structure are experimentally stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Figure 4 presents the number of iterations to minimize the function described by equation (14). During the PSO optimization process, all the solutions converged to the same value.…”
Section: Power Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 presents the number of iterations to minimize the function described by equation (14). During the PSO optimization process, all the solutions converged to the same value.…”
Section: Power Optimizationmentioning
confidence: 99%
“…Establishing the most important parameters that the highest amount of energy is obtained, the optimization process using the PSO algorithm is carried out for the range of the parameters depicted in equation (14).…”
Section: Power Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex unsteady turbulent flow existence in PAT discloses the occurrence a more significant impact of vortex flow pattern. Maximum turbulence is located around trailing edge next to leading edge with lower turbulence located at the suction side [32][33][34][35][36][37]. As rotational speed increases, turbulence increases as well.…”
Section: Pat Flow Instabilities Analysismentioning
confidence: 99%
“…In the early stage, the resonant-based vibration harvesters have been widely used to generate energy, which could only achieve considerable energy harvesting performance at or near its resonant frequency [5,6]. To remedy this problem, many structural optimization designs [7,8] and technologies including resonance tuning technique [9][10][11][12], monostable technique [13][14][15][16][17], bistable technique [18][19][20][21][22] and tristable technique [23][24][25][26][27] have been proposed. Theoretical analysis and experimental results have shown that the nonlinear harvester could improve the ability to harvest energy under certain circumstances.…”
Section: Introductionmentioning
confidence: 99%